Genotoxicity and embryotoxicity of urban air particulate matter collected during winter and summer period in two different districts of the Czech Republic - Binková, B; Veselý, D; Veselá, D; Jelínek, R; Srám, R J (Mutation research, 1999)
This study is the in vitro part of a long-term program to investigate the impact of air pollution on the health of a population in a polluted region of Northern Bohemia. In order to assess the possible health risks associated with a complex mixture of hundreds of organic compounds adsorbed to air particles, we used a biomarker-directed fractionation procedure to evaluate biological activities of different chemical compound classes. The extractable organic compounds from the air particles collected in both the polluted and the control districts during the summers and winters of 1993-1994 were investigated. The principal aim of this study was to compare the DNA binding activities of those compound classes using an in vitro acellular assay coupled with 32P-postlabeling and an embryotoxicity assay using Chick Embryotoxicity Screening Test (CHEST). In both assays, the highest activity was due to the neutral fractions from which the aromatic subfractions containing mainly polycyclic aromatic hydrocarbons (PAHs) and their methyl-derivates were the most active for both localities and seasons. A good correlation between the levels of DNA adduct formation using S9 metabolic activation and the ED50 for all different complex mixtures of organic compounds was observed (r=0.773, p<0.001). DNA adduct maps and high performance liquid chromatography (HPLC) profiles were similar for samples from both districts and seasons. The major DNA adducts resulting from the crude extracts were identical to those derived from aromatic fractions. The DNA adducts tentatively identified constituted about 50% of the total adducts formed by the crude extracts following S9-metabolic activation. Our results confirmed the similarities of the major ubiquitous emission sources of organic compounds in both districts. This is the first report in which the biological activities of complex mixtures in short-term assays with remarkably different endpoints such as DNA adduct formation and embryotoxicity have been compared.
Keywords: Cattle; Embryo, Nonmammalian; Czechoslovakia; adukty DNA; Mutagenicity Tests; vysokoúčinná kapalinová chromatografie; LD50; skot; Urban Population; Mutagens; polycyklické aromatické uhlovodíky; Chromatography, High Pressure Liquid; látky znečišťující vzduch; Polycyclic Aromatic Hydrocarbons; mutageny; testy genotoxicity; radioizotopy fosforu; Animals; lidé; kuřecí embryo; roční období; Seasons; Humans; zvířata; DNA Adducts; Československo; DNA; Phosphorus Radioisotopes; Lethal Dose 50; Chick Embryo; embryo nesavčí; městské obyvatelstvo; Air Pollutants